KAJIAN MANFAAT PENERAPAN ISO 14001 PADA 12 PERUSAHAAN - Muti Sophira Hilman; Ellia Kristiningrum (Badan Standardisasi Nasional, 2008)
The implementation of ISO 14001 gives a lot of benefits for organization, such as improving environmentalperformance, reduce cost and improve market access. From many organizations that have certification of ISO14001, it’s important to know what is the reason of the company in implementation ISO 14001, what is the realbenefit as an impact of implementation ISO 14001 and what is the problem of implementation ISO 14001. Thispaper describes the implementation of ISO 14001 in 12 industries in Indonesia that have ISO 14001 certification.The method of this study is descriptive method, it describes about situation or factual condition. Data collectingtools is by quetioner. Result of this study showed that the first reason to implement of ISO 14001 is for improvingcompany image, benefits of certification ISO 14001 are pollution reduced, reducing the society complaint,increasing the efficiency process, fulfillment of the regulation, increasing on the management activities,increasing the customer satisfaction, and increasing sell of the products. The problems of implementation ISO14001 are lack of top management commitment, lack of participation and awareness of employee, lack ofpromotion and information from management, and the high expense for certification.